A considered application of the Langreth-Lundqvist van der Waals density functional in the context of : open shell molecules, atom centered basis sets, adsorption of graphene into a Bi₂Se₃ slab - Cathcart, Thomas (Trinity College (Dublin, Ireland). School of Physics, 2015)
The work in this thesis is aimed towards exploring the edge case application of the Langreth-Lundqvist vdW density functional (vdW-DF). The increasing popularity of the vdW-DF functional has resulted in its application across a wide variety of systems. Some of these systems are at the limit of the approximations made in the derivation of the functional, so called edge case systems. Although the vdW-DF functional may break down when applied to these edge case systems, through careful exploration of these systems we gain a greater understanding of not only the functional but also ways within which it can be improved.
Keywords: Physics, Ph.D.; Ph.D. Trinity College Dublin